Daylighting handbook. Volume I - Reinhart, Christoph F. (Christoph Frank), 1971-; Stein, Ria (United States : Christoph Reinhart, 2014)
"This is the first volume in a series of upcoming books on daylighting and other sustainable building design concepts." --Cover.
--Introduction -- Fundamentals : Designing for daylight -- The source -- The sensor -- Massing studies -- Designing with the sun : Where is the sun? -- Static shading -- Physical models -- Appendix : Reference office -- Index.
Includes bibliographical references and index.
Keywords: Light in architecture; Daylight